2015
DOI: 10.1101/gad.265215.115
|View full text |Cite
|
Sign up to set email alerts
|

RNF17 blocks promiscuous activity of PIWI proteins in mouse testes

Abstract: PIWI proteins and their associated piRNAs protect germ cells from the activity of mobile genetic elements. Two classes of piRNAs-primary and secondary-are defined by their mechanisms of biogenesis. Primary piRNAs are processed directly from transcripts of piRNA cluster loci, whereas secondary piRNAs are generated in an adaptive amplification loop, termed the ping-pong cycle. In mammals, piRNA populations are dynamic, shifting as male germ cells develop. Embryonic piRNAs consist of both primary and secondary sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 64 publications
6
58
0
Order By: Relevance
“…However, it has later been demonstrated that young, potentially active elements are enriched in pachytene piRNA clusters. These elements show a bias in orientation to enable the production of antisense piRNAs that play a role in suppressing transposons during meiosis , Hirano et al 2014, Wasik et al 2015. In addition to the transposon silencing, pachytene piRNAs have been shown to be involved in the degradation of mRNAs and lncRNAs in late meiotic and haploid cells , Goh et al 2015, Gou et al 2015, Watanabe et al 2015, Zhang et al 2015.…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has later been demonstrated that young, potentially active elements are enriched in pachytene piRNA clusters. These elements show a bias in orientation to enable the production of antisense piRNAs that play a role in suppressing transposons during meiosis , Hirano et al 2014, Wasik et al 2015. In addition to the transposon silencing, pachytene piRNAs have been shown to be involved in the degradation of mRNAs and lncRNAs in late meiotic and haploid cells , Goh et al 2015, Gou et al 2015, Watanabe et al 2015, Zhang et al 2015.…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
“…Therefore, the ping-pong cycle seems to be rather inactive in these cells and pachytene piRNAs are produced mainly by the primary processing pathway. In fact, a Tudor protein RNF17 has been shown to repress secondary piRNA amplification in adult gonads, and the deletion of RNF17 in mice unleashed ping-pong during meiosis and caused aberrant production of piRNAs and degradation of genic transcripts (Wasik et al 2015). Pachytene piRNAs were originally reported to be depleted from transposon sequences (Girard et al 2006).…”
Section: Germ Granules As Platforms For Pirna Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ping-pong signal was determined by calculating the base pair distance between the 5' of piRNAs overlapping in opposite strands (Brennecke et al, 2007). The Z-score was calculated as in Wasik et al (Wasik et al, 2015), and is defined as Z = (P10-M)/SD, where P10 is the number of reads pairs with 10 bp overlap, and M and S are the mean and standard deviation, respectively, of the number of read pairs at with 1-9 and 11-30 overlap. Sense / Antisense bias was determined by calculating the ratio of reads mapping in the same or the opposite strand for each annotated transposable elements (DNA or RNA in repeatmasker).…”
Section: Smallrna-seqmentioning
confidence: 99%
“…Loss of proteins required to make pachytene piRNAs, including the pachytene piRNA-binding protein, MIWI (PIWIL1), invariably arrests spermatogenesis without producing sperm, rendering males sterile (Deng and Lin, 2002;Reuter et al, 2011;Zheng and Wang, 2012;Li et al, 2013;Castañeda et al, 2014;Wasik et al, 2015). Yet loss of the chromosome 17 pachytene piRNA-producing locus, 17-qA3.3-27363(−),26735(+) (henceforth, pi17), has no detectable phenotype or impact on male fertility (Homolka et al, 2015), even though pi17 produces ~16% of all pachytene piRNAs in pachytene spermatocytes.…”
Section: Introductionmentioning
confidence: 99%